2019
DOI: 10.1002/kjm2.12100
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and outcomes of stereotactic vacuum‐assisted breast biopsy for diagnosis and management of nonpalpable breast lesions

Abstract: Stereotactic vacuum‐assisted biopsy (SVAB) is an alternative method of breast biopsy for nonpalpable lesions detected by mammography. Considering the diagnostic effectiveness, a direct comparison of SVAB and open surgical biopsy (OSB) is lacking. We performed a retrospective review of 276 (33.8%) SVAB and 541 (66.2%) OSB to compare the diagnostic accuracy and the total number of procedures the patients underwent. The negative predictive values of OSB and SVAB were 99.77% and 99.61%, and their false‐negative ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…In our study, we found that the distribution of malignancies in BI-RADS category is similar with the standard guideline by American College of Radiology 16 . Our results corroborate with the findings of other studies which showed that the likelihood of malignancy increases with BI-RADS category 7,11,12,17,18 . Although calcifications play a crucial role in early breast cancer diagnosis, they are also associated with 63.2% of benign pathology 7 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, we found that the distribution of malignancies in BI-RADS category is similar with the standard guideline by American College of Radiology 16 . Our results corroborate with the findings of other studies which showed that the likelihood of malignancy increases with BI-RADS category 7,11,12,17,18 . Although calcifications play a crucial role in early breast cancer diagnosis, they are also associated with 63.2% of benign pathology 7 .…”
Section: Discussionsupporting
confidence: 92%
“…We found that the DCIS and ADH underestimation rate of our VABB were in line with previous studies. In a previous study by Tsai et al 11 , the DCIS underestimation rate was 16.7% while another study by Kettritz et al 17 revealed that underestimation of ADH and DCIS were 24% and 12%, respectively. Another recent study by Badan et al reported the underestimation rate of ADH was 25% and DCIS was 14.28% 13 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Also, US-guided localization surgery is more suitable for in situ cancers, invasive cancers which need neoadjuvant therapy and more accurate evaluation of neoadjuvant therapy response (17)(18)(19)(20)(21). Compared to the negative predictive value and false negative rate of open surgical biopsy (99.61% and 4.76%), the negative predictive value of VABB was 99.77% and the false negative rate was 0.96% (22). These results demonstrated that VABB under the guidance of US exhibited the same diagnostic coincidence rate as that of segmental resection.…”
Section: Discussionmentioning
confidence: 99%